PRAKTEK DISKRIMINASI TELKOM GROUP TERHADAP NETFLIX BERDASARKAN HUKUM PERSAINGAN USAHA - Alma Syafitri; Sharda Abrianti (Fakultas Hukum Universitas Trisakti, 2022)
A competition is necessary to motivate business actors and boost the nation's economy. It will, however, have a negative effect if it is carried out by discriminating against some business actors in comparison to all current business actors. In accordance with business competition law, this article investigates instances of discriminatory activities by TELKOM Group against the provision of Netflix internet access services. The issue is whether the criteria for discriminatory activities used by TELKOM Group against Netflix in the Decision on Case Number 08/KPPU-I/2020 can be met, and how can KPPU approach the investigation of suspected discriminatory acts from a legal standpoint. The research method makes use of secondary data, normative analysis of KPPU Decision No. 08/KPPU-I/2020, library research, and data collection methodologies. and qualitative data analysis is used, and deductive reasoning is employed in the conclusion-drawing process. The findings of the study, along with the discussion and conclusion, demonstrate that the TELKOM Group violated the terms of Article 19 letter d of Law No. 5 of 1999 by engaging in discriminatory activities in relation to the blocking of Internet access services for Netflix. KPPU employs the Rule of Reason approach while deciding matters.